The Influence of Person-Organization Fit on Employee Performance at PT. Rimba Borneo Cemerlang - Ridwan Fahrozi; Casilam Casilam; Novitasari Novitasari; Diah Nofitasari (Pasundan Social Science Development, 2025)
This study aims to analyze the influence of Person–Organization Fit on employee performance at PT. Rimba Borneo Cemerlang. The research approach used is quantitative associative with a survey method. The study population includes all 200 employees of PT. Rimba Borneo Cemerlang, with a sample size of 133 respondents determined using the Slovin formula and simple random sampling techniques. Data were collected through a Likert-scale-based questionnaire and analyzed using simple linear regression with the help of SPSS software. The results of the study indicate that Person–Organization Fit has a positive and significant effect on employee performance. This is evidenced by the calculated t value of 3.653 which is greater than the t table of 1.96 with a significance level of 0.001. In addition, the results of the determination coefficient test show an R Square value of 0.441, which indicates that Person–Organization Fit is able to explain 44.1% of the variation in employee performance, while the rest is influenced by other variables outside the research model. This finding confirms that the compatibility between individual values, goals, and characteristics with organizational culture is an important factor in improving employee performance. Therefore, organizations are advised to integrate value alignment into human resource management policies to support the achievement of optimal and sustainable performance.